NILAI-NILAI SOSIAL PADA NASKAH DRAMA (HANYA SATU KALI) DI KANAL YOUTUBE TEATER LANGIT BIRU SMAN 1 SOOKO : KAJIAN SOSIOLOGI SASTRA - Ahlan Romadhona; M. Afif Ardiansyah; Kartika Auliyah; Akhmad Fatoni (CV. Denasya Smart Publisher, 2026)
This study aims to describe the social and religious values contained in the drama script Hanya Satu Kali performed by Teater Langit Biru SMAN 1 Sooko. Using a qualitative descriptive method and a sociology of literature approach, data were collected through repeated reading and note-taking of dialogues and scenes reflecting social and religious aspects. The results show that the drama strongly presents social values such as solidarity, empathy, responsibility, and sacrifice, which shape character interactions and drive the plot. Furthermore, religious values, including patience, sincerity, and spiritual awareness, emerge dominantly through the main character's inner conflict when facing life and death. The integration of these two dimensions offers profound moral and spiritual messages. This study concludes that Hanya Satu Kali is a literary work relevant for character education and can be utilized as an effective medium for literature learning in schools.